2008
DOI: 10.1038/sj.ijo.0803794
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinases 2 and 9 and their tissue inhibitors 1 and 2 in premenopausal obese women: relationship to cardiac function

Abstract: Background: Myocardial fibrosis is one of the mechanisms underlying left ventricular (LV) dysfunction in obese patients and may result from dysregulation of extracellular matrix (ECM) turnover. Matrix metalloproteinases (MMPs) and their tissue inhibitors (TIMPs) represent a regulatory system playing a crucial role in ECM metabolism. Objectives: We sought to assess plasma levels of MMP-2, MMP-9, TIMP-1 and TIMP-2 in obese young women and to evaluate the association between MMP/TIMP system components and LV func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
27
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 45 publications
(57 reference statements)
11
27
0
1
Order By: Relevance
“…The findings reported here confirmed previous findings that showed higher circulating levels of MMP-9 in obese women as compared to lean women [5,10,11]. To our knowledge, we are the first to report a decreased plasma MMP-8 concentration in obese women.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The findings reported here confirmed previous findings that showed higher circulating levels of MMP-9 in obese women as compared to lean women [5,10,11]. To our knowledge, we are the first to report a decreased plasma MMP-8 concentration in obese women.…”
Section: Discussionsupporting
confidence: 92%
“…Excessive production and release of MMP-9 are observed in adipose tissue; this contributes to tissue remodeling and expansion [20] and may contribute to higher plasma MMP-9 levels in obesity [5,10,11]. Clinically, it is important to note that the increased MMP-9 concentrations reported here may increase the risk of cardiovascular diseases in obese women [5,6]; this observation suggests the potential use of this biomarker as a nontraditional cardiovascular risk factor [21].…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…26 Downregulation of MMP-2 activity has been demonstrated in premenopausal obese women, and is associated with attenuated ECM degradation and abnormalities of left ventricular function. 27 Although MMP-2 and MMP-9 are similar enzymes, our results corroborate a study that showed distinct promoter Figure 1 Effect of body mass index (BMI) on matrix metalloproteinase 2 expression in patients with bipolar disorder (during mania and euthymia) and controls Figure 2 Effect of body mass index (BMI) on matrix metalloproteinase 9 expression in patients with bipolar disorder (during mania and euthymia) and controls elements and different spatial and temporal expression patterns of these proteases during ischemia/reperfusion injury. 11 It is possible that the type of upstream stimuli operative in BD will ultimately determine the transcriptional activity of selected MMP types.…”
Section: Discussionmentioning
confidence: 99%
“…MMPs degrade ECM structural proteins (Jun et al, 2011), and TIMPs are the major endogenous regulators of MMP activities in tissues (Kandalam et al, 2011). MMPs and their tissue inhibitors represent a regulatory system that plays a crucial role in ECM metabolism (Kosmala et al, 2008). A previous study found that HG altered the level of MMPs and cytokines in fibroblasts (Westermann et al, 2007).…”
Section: Introductionmentioning
confidence: 99%